The Elbow - Sharma, Ashish K; Khalid, Kamarul Ariffin; Mah, Edward T (Hodder Arnold, an imprint of Hodder Education, an Hachette UK Company, 2012)
The elbow joint has a key role in the functions of the upper limb like feeding, washing and toilet care. Its hinge action and strong static collateral stability, combined with dexterity and versatility of the shoulder, hand and forearm enables the hand to be put in almost any position on the body. The elbow is inherently a stable joint. Both static as well as dynamic factors contribute to its stability. Numerous biomechanical studies have contributed to our understanding of the elbow stabilising factors and elbow dynamics.